THE EFFECT OF CIVICS TEACHER'S ROLE AND EMOTIONAL INTELLIGENCE ON JUVENILE DELINQUENCY - Maulina Rahmawati; Irawan Suntoro; Yunisca Nurmalisa (FKIP Unila, 2012)
This research was aimed to analyze and to test the effect of civics teacher's role on juvenile delinquency of SMA Negeri 15 Bandar Lampung academic year 2012/2013, effect of emotional intelligence on juvenile delinquency of SMA Negeri 15 Bandar Lampung academic year 2012/2013, and the effect of civics teacher's role and emotional intelligence on juvenile delinquency of SMA Negeri 15 Bandar Lampung academic year 2012/2013. Regression model is used to examine the effect between independent variables with the dependent variable. The regression model that is used are simple linear regression and multiple linear regression. The results of this research are: (1) There was negative and significant effect between of civics teacher's role on juvenile delinquency of SMA Negeri 15 Bandar Lampung academic year 2012/2013. (2) There was negative effect of emotional intelligence on juvenile of SMA Negeri 15 Bandar Lampung academic year 2012/2013. (3) There was negative and significant the effect of civics teacher's role and emotional intelligence on juvenile delinquency of SMA Negeri 15 Bandar Lampung academic year 2012/2013. Key Word : Civics Teacher's Role, Emotional Intelligence, Juvenile delinquency.